Vibration Feedforward Compensation for Magnetically Suspended Control and Sensitive Gyroscope with Spherical Rotor - Qiang Liu; Heng Li; Cong Peng; Sha Sheng; Zhaojing Yin; Zhiguo Liu (Shock and Vibration)
Magnetically suspended control and sensitive gyroscope (MSCSG) with two capabilities including attitude control and attitude measurement is promising in meeting the requirements of novel spacecraft. When the momentum vector of a high-speed rotor suspended in five directions is tilted by Lorentz force-type magnetic bearing, the instantaneous large control moment is obtained. The spacecraft attitude can be sensed by a high-speed rotor without deflection interference torque. In this paper, a novel MSCSG with sphere rotor is presented, and its spherical structure and working principle are introduced. The magnetic bearing-rotor dynamic model is established based on Newton’s second law and the gyrokinetic equations. The generating mechanism of three interferences, including bearing dynamic reaction force, deflection torque, and centrifugal force, is analyzed. The feedforward compensation control against three interferences for MSCSG is adopted, and the loading sequence of three interferences is simulated. The optimal sequence of bearing dynamic reaction force, deflection torque, and centrifugal force is used. The radial and axial vibration displacement amplitudes are reduced from 20.8 μm and 31.7 μm to 9.4 μm and 14.9 μm, respectively. The experimental results are in good agreement with the simulation, which indicates the MSCSG rotor unbalance vibration is suppressed effectively by the feedforward compensation method.